Fluorescence lifetime excitation cytometry by kinetic dithering. Issue 12 (12th May 2014) - Li, Wenyan; Vacca, Giacomo; Castillo, Maryann; Houston, Kevin D.; Houston, Jessica P.; Lapizco‐Encinas, Blanca H.; Davalos, Rafael V.
<x xml:space="preserve">Abstract</x> Flow cytometers are powerful high‐throughput devices that capture spectroscopic information from individual particles or cells. These instruments provide a means of multi‐parametric analyses for various cellular biomarkers or labeled organelles and cellular proteins. However, the spectral overlap of fluorophores limits the number of fluorophores that can be used simultaneously during experimentation. Time‐resolved parameters enable the quantification of fluorescence decay kinetics, thus circumventing common issues associated with intensity‐based measurements. This contribution introduces fluorescence lifetime excitation cytometry by kinetic dithering (FLECKD) as a method to capture multiple fluorescence lifetimes using a hybrid time‐domain approach. The FLECKD approach excites fluorophores by delivering short pulses of light to cells or particles by rapid dithering and facilitates measurement of complex fluorescence decay kinetics by flow cytometry. Our simulations demonstrated a resolvable fluorescence lifetime value as low as 1.8 ns (±0.3 ns) with less than 20% absolute error. Using the FLECKD instrument, we measured the shortest average fluorescence lifetime value of 2.4 ns and found the system measurement error to be ±0.3 ns (SEM), from hundreds of monodisperse and chemically stable fluorescent microspheres. Additionally, we demonstrate the ability to detect two distinct excited state lifetimes from fluorophores in single cells using FLECKD. This approach presents a new ability to resolve multiple fluorescence lifetimes while retaining the fluidic throughput of a cytometry system. The ability to discriminate more than one average fluorescence lifetime expands the current capabilities of high‐throughput and intensity‐based cytometry assays as the need to tag one single cell with multiple fluorophores is now widespread.